30 Do nice guys finish last?. Issue 12 (23rd November 2017) - Turner, Chris; Turner, Jake
Abstract : Emergency medicine is widely recognised as an intense specialty. Interruptions are known to derail thoughts, increasing cognitive load and result in longer periods before deep thought is re-established. Although approachability and warmth are regarded as important factors in clinicians we wondered what impact these characteristics had on the number of interruptions. Methodology: A team of 6 medical students were trained in the use of abespoke tool to record shop floor activities. Over 4 months we conducted 100 hours of minute by minute time and motion study of emergency medicine consultants during their clinical shifts, and noted how often they were interrupted. At the end of shifts the assessors were asked a set of qualitative questions on the behaviour and attitudes of the consultants. These questions were completed in seclusion and in an anonymous format, to minimise the chance of bias/influence. Questions included: 'How friendly was the consultant with other staff?' 'How friendly was this consultant with patients?' And, 'How would you rate this consultant's 'general positivity'?' We then assessed whether consultants that scored 'higher' inthese areas were more likely to be interrupted. Our hypothesis was that consultants who were more friendly were less intimidating for juniors and nurses to approach with questions, and so may suffer from an increase in cognitive load due to being interrupted and questioned more frequently than consultants who were felt to be less approachable. We found that consultants who scored 1(highest) in friendliness had an average of 7.38 interruptions per hour, compared to consultants who scored 3 or greater, who had an average of 3.59. Conclusions: Our average interruptions were close to those found in previous publications (between 6 and 9 interruptions per hour), however there was a large amount of inter-consultant variability, with one consultant during one shift being interrupted over 12 times per hour on average. If the results of this study are replicable, then it may raise questions about how best to manage this extra cognitive load. Although some may argue that being seen as slightly less friendly has an advantage in the reduction of interruptions, this may come at a cost to patient safety. There is clearly a fine balance to be made.